Belize : Staff Report for the 2011 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2011)
The 2011 Article IV Consultation report concludes that Belize has weathered the financial crisis relatively well when compared with Caribbean Community peers. Executive Directors have commended the authorities for their macroeconomic management, which enabled Belize to weather the financial crisis. Although the near-term outlook is positive, challenges arise from the uncertain global environment, rising gross financing needs of the public sector, and the weak investment climate. Directors have emphasized the need to tighten further the fiscal stance and rebuild macroeconomic buffers.